Introduction to SQL Server query optimization : understanding query optimization and built-in optimization tools - Pollack, Edward, (Database administrator) (Apress, 2019)
"Begin your journey into query optimization by learning the basics of how SQL Server processes a query from start to finish. Once this foundation is established, you will focus on execution plans: What are they? How do we read them? And what are their more common operations? A variety of statistics options will be introduced that provide insight into query duration and the load that a given query presents on memory and storage resources. With a set of tools defined, you will tackle a variety of common optimization challenges. You'll review some common problems in which performance is inadequate and then solutions to mitigate those problems and improve performance. These basic patterns will provide a format for viewing and analyzing queries with the goal of being able to identify the source of the problem when a query is running too slow."--Resource description page